Resource relatedness and the mode of entry into new businesses: Internal resource accumulation vs. access by collaborative arrangement. (18th August 2014) - Speckbacher, Gerhard; Neumann, Kerstin; Hoffmann, Werner H.
<x xml:space="preserve">Abstract</x> When firms seek to enter a new business segment, they have to decide how to best gain access to the required resources. This paper analyzes how resource relatedness influences a firm's decision between internal development and collaborative arrangement as modes of entry. We distinguish between a firm's capacity to transfer its established resources to the new segment (resource transferability) and the integration and synergistic combination of current firm resources with target segment resources in day‐to‐day operations (resource complementarity). Resource transferability makes entry by internal development more likely, but this effect depends on segment characteristics. Synergies from complementary resources can be exploited more easily within firm boundaries than across an alliance interface. However, certain partner characteristics can substitute in part for belonging to the same firm. Copyright © 2014 John Wiley & Sons, Ltd.